INTERACTIVE PROMOTION INSTRUMENTS AS A TREND IN RETAIL COMMUNICATIONS SOLUTIONS - V. Starostin; V. Chernova (Вестник университета)
This article reviews the usage of interactive instruments that become a developing trend in modern retail sector. In the last few years more retail companies start to integrate interactive format of communications in real business practice. Interactive marketing communications allow narrow targeting for the audience which helps to attract attention to the specific retail segment, improve customer loyalty and economic wealth of the company. That type of communications has all sorts of expected advantages that are focused to: attract customer attention, stimulate call to action, generate positive brand image, inform and educate the customer.